2023
DOI: 10.1007/s00210-023-02552-z
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic acid, the active component of Rubi Fructus, induces apoptosis of SGC-7901 and HepG2 cells through mitochondrial pathway and exerts anti-tumor effect

Abstract: Rosmarinic acid (RA) is a well-known phenolic acid widely present in over 160 species of herbal plants and known to exhibit anti-tumor effects on breast, prostate, and colon cancers in vitro. However, its effect and mechanism in gastric cancer and liver cancer are unclear. Moreover, there is no RA report yet in the chemical constituents of Rubi Fructus (RF). In this study, RA was isolated from RF for the first time, and the effect and mechanism of RA on gastric and liver cancers were evaluated using SGC-7901 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Carnosol can directly inhibit the chymotrypsin‐like activity of the 20S proteasome and the expression of matrix metalloproteinase‐9 (MMP‐9), thus achieving the migration inhibition of cancer cells (Allegra et al., 2020). Rosmarinic acid (RA) is a potent apoptosis inducer of SGC‐7901 and HepG2 cells via the mitochondrial pathway (Chen et al., 2023), and it has also been shown to inhibit cytokine‐induced mesangial cell proliferation and suppress platelet‐derived growth factor (PDGF) and c‐myc mRNA expression in PDGF‐stimulated mesangial cells in vitro (Makina et al., 2002). In addition, many pharmacological studies have shown that the bioactive compositions of flavone 4,7‐ O ‐dimethylapigenin, 7‐ O ‐methyl‐epi‐rosmanol, carnosol, carnosic acid, and betulinic acid in rosemary were able to block the activation of AhR by TCDD, thus inhibiting the cancer cell proliferation (Kallimanis et al., 2022).…”
Section: Biological Activities Of Rosemary Extractmentioning
confidence: 99%
“…Carnosol can directly inhibit the chymotrypsin‐like activity of the 20S proteasome and the expression of matrix metalloproteinase‐9 (MMP‐9), thus achieving the migration inhibition of cancer cells (Allegra et al., 2020). Rosmarinic acid (RA) is a potent apoptosis inducer of SGC‐7901 and HepG2 cells via the mitochondrial pathway (Chen et al., 2023), and it has also been shown to inhibit cytokine‐induced mesangial cell proliferation and suppress platelet‐derived growth factor (PDGF) and c‐myc mRNA expression in PDGF‐stimulated mesangial cells in vitro (Makina et al., 2002). In addition, many pharmacological studies have shown that the bioactive compositions of flavone 4,7‐ O ‐dimethylapigenin, 7‐ O ‐methyl‐epi‐rosmanol, carnosol, carnosic acid, and betulinic acid in rosemary were able to block the activation of AhR by TCDD, thus inhibiting the cancer cell proliferation (Kallimanis et al., 2022).…”
Section: Biological Activities Of Rosemary Extractmentioning
confidence: 99%
“…These cells constitute TNBC, an aggressive and metastatic subtype unaffected by hormone therapy [ 33 ]. We present a range of integrated chemical biology techniques aimed at using relevant mechanisms of action that might lead to major therapeutic advancements in the treatment of BC [ 3 , 4 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%